A comparative study of multimedia teaching and learning materials between fully residential and daily smart school / Mohd Isma Karman Shah Ismail - Ismail, Mohd Isma Karman Shah (2005)
The implementation of Information and Communication Technology (ICT) in education becomes the vital effort of our government in order to improve the level of education in our country. Multimedia teaching and learning have become one of them that are being seriously implemented in nowadays education area. The government also introduced the smart school programs which become the platform in order to achieve the excellent outcome in education. This thesis presents the result of comparative study of multimedia teaching and learning materials between fully residential and daily smart school. The objectives of this research are to study the effectiveness of multimedia implementation as teaching and learning materials between the fully residential and the daily smart school and identify any factors that can improve it. Questionnaires have been distributed in order to gather primary data from the two selected smart schools which are one fully residential school and another one daily school. The implementation of multimedia as teaching and learning materials between these two smart schools was compared based on the concepts, effects, benefits and problems arise during the implementation. This thesis also provides several suggestions and recommendations in order to improve the use of multimedia implementation in smart school.